Behavioral interventions in cognitive behavior therapy : practical guidance for putting theory into action - Farmer, Richard F. (Psychology professor); Chapman, Alexander L. (Alexander Lawrence) (American Psychological Association, 2016)
"Although cognitive behavior therapy (CBT) is the most widely practiced evidence-based clinical approach in mental health today, CBT is a broad term that encompasses a wide array of approaches and techniques that can be difficult for even experienced clinicians to navigate. In this fully updated edition, the authors provide a detailed, step-by-step guide to behavioral interventions in CBT. They discuss case formulation and treatment planning, core behavioral intervention strategies, and innovative approaches such as acceptance, mindfulness, and a behavioral approach to cognition. They look at key behavioral techniques, such as self-monitoring, behavioral activations, exposure therapy, and skills training, that are essential features of CBT practice. The behavioral framework they describe is practical and accessible to clinicians and students with varying degrees of behavioral training. Alongside a comprehensive update of the research literature, this edition features new chapters on enhancing interpersonal effectiveness, emotion regulation, and navigating particularly difficult therapeutic challenges"--Publicity materials. (PsycINFO Database Record (c) 2015 APA, all rights reserved).